Two-axis tracking solar irradiance measurements at Tromsø - Hansen, Jakob Holden (UiT The Arctic University of Norway, 2020)
The world is changing towards using more renewable, rather than fossil energy sources in order to reach the 1.5 degrees celsius goal of the Paris agreement (Merchant, 2018). This thesis’ main focus is to investigate the solar irradiance in Tromsø using 2-axis tracking measurements from May 2020. The reduction of global irradiance and direct irradiance is also compared against the values of the other European cities, and the diffuse and clearness index is calculated. A comparison between Skartveit & Olseth (S&O) model and measurements in Tromsø is made. The aim of the thesis is to investigate atmospheric scattering and absorption of sunlight in Tromsø and to comparethese results with measurements from other cities. The S&O comparison show a low accuracy between modelled values and actual measured values for diffuse and clearness index. The global horizontal irradiance (GHI) and direct normal irradiance (DNI) is compared with the extraterrestrial irradiance. Compared to other European cities, the reduction of GHI show that Tromsø have 5% less mean reduction, meanwhile the DNI reduction have an increased mean value of 10%. Conclusively, it can be shown that Tromsø has higher global irradiance values for given solar elevation angles, when compared to the other European cities.